Characteristics and treatment patterns of relapsed/refractory diffuse large B-cell lymphoma in patients receiving ≥3 therapy lines in post-CAR-T era. (3rd October 2021) - Xie, Jipan; Wu, Aozhou; Liao, Laura; Nastoupil, Loretta J.; Du, Ella Xiaoyan; Noman, Ahmed; Chen, Lei
Abstract: Objective: Several novel treatments have been approved for relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL) since chimeric antigen receptor T-cell (CAR-T) therapy became available. The objective of this study was to describe characteristics and treatment patterns in patients with R/R DLBCL post-CAR-T approval. Methods: Adult patients with R/R DLBCL who initiated third-line treatment or later (3 L+) since 18 October 2017 were identified using administrative claims from IQVIA PharMetrics Plus (1 January 2014–31 March 2020). Treatments were categorized as chemotherapy/chemoimmunotherapy (CT/CIT), targeted therapies, CAR-T and stem cell transplant (SCT). Treatment distribution, treatment duration of CT/CIT and targeted therapies, and initiation of next-line therapy were described for patients receiving 3 L; analyses were repeated for 4 L. Results: A total of 145 patients received 3 L between 18 October 2017 and 31 March 2020. Mean age was 57 years, and 34% were female. CT/CIT (44.9%), targeted therapies (26.9%), CAR-T (17.2%) and SCT (11.0%) were administered in 3 L. The median treatment duration was 2.9 months for CT/CIT and targeted therapies combined. 31% of patients initiated 4 L within a median follow-up of 5.8 months. Among patients who received 4 L ( N = 55), targeted therapies were most commonly used (36.4%), and the median treatment duration was 2.5 months. Conclusions: Post-CAR-T approval, the majority of patients were treated with CT/CIT or targeted therapies in 3 L and 4 L, though most of the targeted therapies prescribed are not indicated for DLBCL. Treatment duration was short. A high proportion of patients moved to the next line of therapy (LOT) during a short follow-up period. This study highlights the unmet need for more effective treatments for patients with R/R DLBCL in 3 L+.